Is the Dark Web Legit? The Case of Dark Web Search Engines - Gehl, Robert William (AoIR Selected Papers of Internet Research, 2016)
One of the most controversial networking technologies available today is the "Dark Web." The Dark Web includes collections of Web sites (i.e., HTML, CSS, PHP, MySQL, and Javascript software) that are only accessible with special routing software. The most popular of these systems – and perhaps the most infamous – is Tor, which enables "hidden services," or Web sites only accessible with the Tor Browser. There are other systems, however: the Invisible Internet Project (i2p), whose router allows access to hidden "eepsites", and Freenet, whose router allows access to Freesites. For some, the Dark Web is decidedly illegitimate: it is a haven of drug dealers, scammers, thieves, and traders of child abuse images. For others, it is a legitimate protector of free speech, allowing whistleblowers like Edward Snowden to expose government excesses and citizens to debate controversial issues without fear of being monitored. In other words, the Dark Web, I suggest, is going through a trial of legitimacy. Is it legitimate, or not? This presentation seeks to answer this question by drawing on three theories of legitimacy, proposing a symbolic/material economy of legitimacy, and then exploring the case of Dark Web search engines. I ultimately argue that the economy of legitimacy apparent in Dark Web search can be found in other Dark Web-based practices, including social networking sites, markets, and network protocol development. Therefore, I suggest future lines of Internet research that can explore the Dark Web.